The influence of exercise-induced fatigue on cognitive function - Moore, R. D.; Romine, M. W.; O'Connor, P. J.; Tomporowski, P. D. (Journal of Sports Sciences, 2012)
Although anecdotal reports suggest that information processing and decision making is impaired immediately following prolonged periods of physical activity, results obtained from laboratory studies of exercise-induced fatigue have been inconsistent. Fatigue effects may be task specific and related to the time of post-exercise testing. The present study examined the effects on adults' performance of two cognitive tasks that differed in processing demands over an 80-min period of fatigue. Thirty young adult men and women were randomly assigned to either an exercise group and completed a 60-min bout of cycle ergometry at 90% ventilatory threshold or a control group and rested for 60 min. Following interventions, each participant completed a simple and complex version of a visual perceptual discrimination test, a 40-min memory-based vigilance test and a repetition of the visual perceptual discrimination tests. Those who exercised evidenced significant decrements in performance on complex perceptual-discrimination tasks compared to participants who rested. The response time of exercisers during a memory-demanding vigilance test were significantly slower than those of participants who rested; however, detection performance did not differ between groups neither was there a decrease in target detection across the vigil. The effects of exercise-induced fatigue may be task specific, with greater effects on perceptual tasks, which involve relatively automatic processing, compared to effortful memory-based tasks.